2010
DOI: 10.3329/jhpn.v28i2.4889
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biological, Social and Psychological Factors on Abnormal Eating Attitudes among Female University Students in Brazil

Abstract: The objective of the study was to estimate abnormal eating attitudes influenced by associated factors among female students of the Universidade Federal de Santa Catarina, Florianópolis, southern Brazil. Abnormal eating attitudes were investigated using the eating attitudes test (EAT-26), according to the presence (EAT+) and absence (EAT-) of symptoms in a sample of 220 students. The body-image was assessed by the bodyshape questionnaire (BSQ-34). Body mass index, body-fat percentage, waist-circumference, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Moreover, the study conducted by Costa et al (2010) found that body dissatisfaction was the only variable among those studied (body dissatisfaction, BMI, body fat percentage, waist circumference and socioeconomic characteristics -monthly family income, monthly per capita income and parents' level of education) that presented a significant association with the presence of disordered eating behaviors. Thus, body dissatisfaction is recognized as one of the main factors that can cause eating disorders.…”
Section: Ohara Et Al (2014)mentioning
confidence: 93%
“…Moreover, the study conducted by Costa et al (2010) found that body dissatisfaction was the only variable among those studied (body dissatisfaction, BMI, body fat percentage, waist circumference and socioeconomic characteristics -monthly family income, monthly per capita income and parents' level of education) that presented a significant association with the presence of disordered eating behaviors. Thus, body dissatisfaction is recognized as one of the main factors that can cause eating disorders.…”
Section: Ohara Et Al (2014)mentioning
confidence: 93%
“…Pembentukan dan perubahan sikap tidak terjadi dengan sendirinya atau dengan sembarangan, tetapi pembentukannya senantiasa berlangsung dalam interaksi manusia dan berkaitan dengan objek tertentu. Menurut Costa & Vasconcelos (2010) pembentukan sikap dipengaruhi beberapa faktor, yaitu faktor biologis yang mencakup usia dan status kesehatan, faktor psikologis, dan faktor komunikasi sosial. Faktor fisiologis seseorang akan menentukan bagaimana sikap seseorang dalam mengambil keputusan.…”
Section: Efektifitas Edukasi Dengan Menggunakan Media Pembelajaran Au...unclassified